Use projection pursuit regression and neural network to overcome curse of dimensionality - ابراهيم, عمر عبد المحسن; حسن, زينة ابراهيم (Journal of Economics and Administrative Sciences, 2018)
AbstractThis research aim to overcome the problem of dimensionality by using the methods of non-linear regression, which reduces the root of the average square error (RMSE), and is called the method of projection pursuit regression (PPR), which is one of the methods for reducing dimensions that work to overcome the problem of dimensionality (curse of dimensionality), The (PPR) method is a statistical technique that deals with finding the most important projections in multi-dimensional data , and With each finding projection , the data is reduced by linear compounds overall the projection. The process repeated to produce good projections until the best projections are obtained. The main idea of the PPR is to model the multiple regression as a sum of the nonlinear functions of the linear structures of the variables. Two approaches were used to solve the problem curse of dimensionality : the first approach is proposed projection pursuit regression method (PPR)  and The second approach is the method of neural networks (NN) representing by (Back Propagation of error)  which is one of the methods used in reducing dimensions . A simulated study was conducted to compare the methods used. The simulations were based on findings that showed that the method (NN) in this study gave better results than the (PPR) based on RMSE.